NeuroEM special interest group: bridging the gap in neurological emergency - Itam @ Ismail, Iskasymar; Yahaya, Siti Nasrina; Baharuddin, Kamarul Aryffin; Sinniah, Vilasini A/p; Harvendhar Singh, Gurjeet Singh; Wan Mohamad, Wan Syahmi; Shah Junit, Mohd Nadzrul Shah; Kandasamy, Regunath; Wan Zaidi, Wan Asyraf; Fitzrol, Diana Noma; Chow, Chee Tong (College of Emergency Physician Academy of Medicine Malaysia (CEP AMM), 2024)
The Neuroemergency Special Interest Group (NeuroEM SIG) was founded in 2022 to address knowledge and skill gaps in neurological emergency management within Malaysia’s emergency medicine sector. Since the inception of Malaysia’s postgraduate emergency medicine training program in 1998, the field has advanced significantly, including the formation of 11 Special Interest Groups. NeuroEM SIG’s mission is to foster multidisciplinary collaboration among emergency physicians, neurologists, and neurosurgeons to enhance the rapid recognition and intervention of neurological emergencies. Through initiatives like the Malaysia Emergency Neurological Life Support (MyENeLS) and Neurological Emergency Exclusive Updates Series (NExUS), NeuroEM SIG has trained approximately 170 healthcare professionals across disciplines and borders, supporting ASEAN countries like Indonesia and the Philippines. Additionally, NeuroEM SIG has hosted national symposiums and virtual continuous medical education sessions, accumulating 33 hours of accessible online learning for healthcare providers. Feedback has underscored the efficacy of these efforts in reducing “neurophobia,” fostering confidence, and developing competence in neurological emergency management. NeuroEM SIG aspires to cultivate a lasting impact on emergency medicine by addressing the crucial need for specialized neurological care knowledge and bridging interdisciplinary gaps in patient care.